Broadband regenerative amplifier based on Ho:CALGO at 2.1 μm - Suzuki Anna; Ahmed Shahwar; Wang Yicheng; Tomilov Sergei; Saraceno Clara J. (EPJ Web of Conferences)
We present a broadband Ho:CALGO regenerative amplifier operating at 2.1 μm, delivering a pulse energy of 342 μJ at 1 kHz with a spectral bandwidth of 5 nm, supporting sub-ps pulse duration.